2011
DOI: 10.1097/mop.0b013e32834c9282
|View full text |Cite
|
Sign up to set email alerts
|

Common neurological co-morbidities in autism spectrum disorders

Abstract: Purpose of Review Autism Spectrum Disorders (ASD) are heterogeneous neurodevelopmental disorders associated with various co-morbidities. Neurological co-morbidities include motor impairments, epilepsy and sleep dysfunction. These impairments are receiving more attention recently, perhaps because of their significant impact on the behavior and cognitive function of children with ASD. Here, we review the epidemiology, etiology and clinical approach to these neurological co-morbidities and highlight future resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 77 publications
(75 reference statements)
2
55
0
6
Order By: Relevance
“…Communication deficits and repetitive behaviors are seen in autism along with various symptoms that can vary in severity, including seizures and increased anxiety (Maski et al, 2011; Fung and Hardan, 2014). Considering almost innumerable genetic, environmental, or a combination of both factors may contribute to the etiology of a single case of autism spectrum disorder, approaches examining central points of cellular signaling and activity may hold promise to direct efforts towards unifying elements of cellular dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…Communication deficits and repetitive behaviors are seen in autism along with various symptoms that can vary in severity, including seizures and increased anxiety (Maski et al, 2011; Fung and Hardan, 2014). Considering almost innumerable genetic, environmental, or a combination of both factors may contribute to the etiology of a single case of autism spectrum disorder, approaches examining central points of cellular signaling and activity may hold promise to direct efforts towards unifying elements of cellular dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…This would provide a more detailed understanding of the relative strengths and weaknesses in this group later in childhood than is usually reported. Hilton et al (2011) reported significant correlations between motor functioning and scores on the Social Responsiveness Scale (SRS; Constantino & Gruber, 2005), a parent report measure of autistic social traits, with more severe symptoms predicting greater motor impairments in the affected siblings, and recent reviews have reported an association between motor impairment and overall symptom severity in ASD (Jeste, 2011;Maski et al, 2012). Other studies have reported face processing deficits or atypicalities in individuals with ASD (e.g., Adolphs et al, 2001;Dawson et al, 2005;Klin et al, 1999;Riby et al, 2007) and in at-risk siblings (Elsabbagh et al, 2012;Elsabbagh et al, 2009;McCleery et al, 2009).…”
mentioning
confidence: 99%
“…Symptoms from the underlying disorder that is predisposing to RBD (eg, a child with autism may have poor eye contact, an odd speech pattern, prefer to play with toys rather than other children, and exhibit stereotyped hand flapping or toe walking. 20 The patient with Smith Magenis syndrome is aggressive or hyperactive during the daytime, and shows mildly dysmorphic facial features in the form of square-shaped forehead, low-set ears, and brachycephaly. 21 It is related to a microdeletion or mutation in the retinoic acid-induced 1 (RAI1) gene.…”
Section: Clinical Manifestationsmentioning
confidence: 99%